Knowledge, Attitude and Practice regarding Malaria Control among Suspected Cases at Selected Primary Health Care in Cox’s Bazar - Barua, Pearly; Barua, Nobel; Chandra Barua, Pravat (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: As part of Sustainable Development Goal Malaria is aimed to zero indigenous transmission among country within 2030 and as part of this elimination from Cox’s Bazar planned within 2025.This study aimed to assess Knowledge, Attitude and Care Seeking as well as reported cleanliness practice among suspected malaria patients to enhance chance from control to elimination phase. Materials and methods: A cross sectional survey was conducted on 127 participants following convenient sampling who attended selected primary healthcare of endemic area during September to October 2023. A pretested semi structured questionnaire was used and data analysis done by excel following SPSS26. Results: Age range between 18-80 years with a mean (±SD) age of 35.95 (±14.32) years. 55.12% were male and 48.8% were poor.Though all participants had heard about malaria,95.3% correctly answered that only mosquito bites transmit malaria, 92.1% could mention at least one malaria symptom but only 7.9% knew they need to test within first 48 hours. When 86.6% reported owning a bed netbut 53.5% reported sleeping under a net. Outof 127 participants, 45.7% had good knowledge of malaria, 36.2% had good practice regarding malaria preventive measures, and 44.9% had a positive attitude regarding malaria. Conclusions: Overall, the study found some evidence gap in Care seeking and reported cleanliness prevention practices although there is reasonable knowledge and positive attitude present. Chatt Maa Shi Hosp Med Coll J; Vol.23 (2); July 2024; Page 74-78